Penetrating aortic ulcer: defining risks and therapeutic strategies - Bischoff, Moritz; Geisbüsch, Philipp; Peters, Andreas; Hyhlik-Dürr, Alexander; Böckler, Dittmar (Herz, 2011)
In addition to classic aortic dissection and intramural hematoma, acute aortic syndrome also includes penetrating aortic ulcers (PAU). The recent advent of highly detailed axial imaging allows closer assessment of PAU and its pathophysiology. However, there is still ongoing discussion about the natural history of the disease, leading to challenging questions concerning the optimal treatment strategy, particularly in asymptomatic patients. In this review, current indications for treatment, with an emphasis on PAU repair in the endovascular era, are discussed.